1997
DOI: 10.1111/j.1440-1827.1997.tb04543.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple gastric lipomas: Report of an asymptomatic case found at autopsy

Abstract: Gastric lipomas are uncommon lesions, usually single and located in the antrum. Common symptoms include upper digestive bleeding, anemia, and intestinal obstruction. Alternatively, they may remain asymptomatic, and detectable only at autopsy. A case of a 72-year-old man, who died of myocardial infarction, was found at autopsy to have multiple gastric lipomas of the corpus and antrum, with a single lesion measuring 10 x 6.5 x 3 cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 2 publications
0
8
0
1
Order By: Relevance
“…Gastric lipomas are rare, bening tumors that on edoscopic examination present a smooth, well defined margin, often present as an oval or spherical submucosal mass composed of well differentiated adipose tissue surrounded by a fibrous capsule [[3], [4], [5], [6]]. Gastric lipomatosis is characterized by multiple gastric lipomas or diffuse gastric infiltration on submucosal or subserosal layer by adipose tissue [[7], [8], [9]]. Previous reports described diffuse infiltration of the submucosal layer by adipose tissue as a pathologic process and suggested that the term “lipomatosis or lipohyperplasia of intestine” should be replace the term “lipoma of intestine” [1,2,10,11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gastric lipomas are rare, bening tumors that on edoscopic examination present a smooth, well defined margin, often present as an oval or spherical submucosal mass composed of well differentiated adipose tissue surrounded by a fibrous capsule [[3], [4], [5], [6]]. Gastric lipomatosis is characterized by multiple gastric lipomas or diffuse gastric infiltration on submucosal or subserosal layer by adipose tissue [[7], [8], [9]]. Previous reports described diffuse infiltration of the submucosal layer by adipose tissue as a pathologic process and suggested that the term “lipomatosis or lipohyperplasia of intestine” should be replace the term “lipoma of intestine” [1,2,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of gastric lipomatosis remains to be established. Postulated etiological factors include embryonic displacement of adipose tissue, congenital predisposition, degenerative disease with disturbance of fat metabolism, post-chemotherapeutic fat deposition, chronic irritation such as chronic inflammatory bowel disease, low-grade infection and hamartomatous syndromes [[12], [13], [14]]. Cabaud and Harris [15] proposed that a fatty lesion with an annular nature and complete lack of encapsulation is a fatty infiltration rather than a true neoplasm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although gastrointestinal bleeding generally presented as chronic blood loss, 2 patients had acute severe blood loss resulting in emergency presentations. (4,5) Two of the 10 patients died due to massive gastrointestinal bleeding. The 9 case reports of multiple lipomas described encapsulated tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Three-quarters of all gastric lipomas occur in the antrum; most of them are located in the submucosa, the remainder being usually subserosal (30). Although gastric lipomas tend to be relatively small, a large lesion measuring 10 ern in the greatest diameter has recently been described as a well circumscribed sessile polyp arising in the submucosa of the antrum (31). Gastric lipomas usually appear soft and yellowish on the cut surface and consist of mature fat tissue divided into lobules.…”
Section: Discussionmentioning
confidence: 99%